In vitro evaluation of the effect of combined indigenous antagonistic bacteria against Fusarium oxysporum - Gallyndra Fatkhu Dinata; Luqman Qurata Aini; Abdul Latief Abadi (Hasanuddin University, 2023)
This study aimed to evaluate the potential of combined indigenous antagonistic bacteria against Fusarium oxysporum f.sp. cepae by in vitro. These bacteria were originated from coffee plant litter in UB Forest and already known their ability as a single biocontrol against F. oxysporum. The research was conducted at the Plant Disease Laboratory, Department of Plant Pests and Diseases, Brawijaya University. The methods consisted of isolate preparation, pathogenicity test and in vitro antagonistic test using a modified multiple culture method. The study was conducted with eight treatments and four replications. Based on this study, there were four best treatments in inhibiting the mycelia growth of F. oxysporum more than 50% compared to the control. The highest inhibitory was Bacillus mycoides and Alcaligenes faecalis which were able to inhibit F. oxysporum up to 67,46%. This study proves the potential of a new combination of indigenous antagonistic bacteria to inhibit fusarium wilt disease.